Carmen [videorecording (DVD)] - Millepied, Benjamin; Dinelaris, Alexander; Barrère, Loïc; Barrera, Melissa, 1990-; Mescal, Paul, 1996-; Palma, Rossy de; Da Silva, Nicole; Hardie, Benedict; Pataky, Elsa, 1976-; D.O.C. (Musician); Mérimée, Prosper, 1803-1870; Pushkin, Aleksandr Sergeevich, 1799-1837 (Sony Pictures Home Entertainment, 2023)
A young dancer is forced to flee the Mexican desert when her mother is murdered. She joins up with a soldier recovering from PTSD and the two begin a passionate love affair in this evocative drama.